EFFECT OF CAGE DENSITY ON FEED INTAKE, BODY WEIGHT GAIN, AND FEED CONVERSION IN BROILER - Dudus Hariadi Budiarta; Edhy Sudjarwo; Nur Cholis (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
The objective of this research was to observe the effect of cages density on broiler chickens during the maintenance period. The materials used in research werebroilerLohmann strain 744 without gender differentiated and maintained for 35 days.In the course of this study, treatment was conducted with broiler cage size of 1 m2. At observations P1 barrier filled 28 chickens, at P2 barrier filled 30 chickens, at P3barrier filled 32 chickens, and at P4 barrier filled 34 chickens. The variables observed in this study is the feed intake consumption, body weight, and feed conversion in broilers. All the data were analyzed by using analysis of variance with Completely Randomized Design (CRD). If there is a significant difference between the treatments then followed by Duncan’s Multiple Range Test.The results of this study indicate that the level of effect that the cage density were significantly different ( P < 0.05 ) on feed consumption and provide a highly significant effect ( P < 0.01 ) on body weight and feed conversion broilers. Based on the results of this study concluded that the density of cages that are too high can affect the appearance of the broiler production. Keywords: Broiler, cages density, body weight and feed conversion.